Joint operation rules considering the uncertainty of energy available for multiple cascaded hydropower system. (19th October 2022) - Wu, Xinyu; Cheng, Ruixiang; Cheng, Chuntian; Ying, Qilin
Abstract: Multi‐reservoir operation rules have been widely used in practice operation. The operation rules are often derived from historical or simulated run‐off information through implicit stochastic optimization or parameterization‐simulation‐optimization. The output decisions of operation rules are usually obtained without considering inflow forecasting or using perfect runoff forecast information, which is hardly implemented in practical applications. This paper proposes robust joint operation rules for multiple cascaded reservoirs considering the uncertainty of energy available. The rule parameters are optimized using multi‐step genetic algorithm for minimum‐power maximization. A case study for a three‐cascaded‐reservoirs system shows that, compared with deterministic joint operation rules, the accuracy of energy available estimation of joint operation rules is increased by 2.3%, considering inflow uncertainty. The simulated minimum‐power decision of joint operation rules considering the uncertainty of energy available is 40.4% higher than that of determinate joint operation rules. Results indicate that there is a possibility of obtaining greater and more effective power decisions through the joint operation rules considering the uncertainty of available energy.